Cost-effectiveness analysis of a community paramedicine programme for low-income seniors living in subsidised housing: the community paramedicine at clinic programme (CP@clinic). Issue 10 (27th October 2020) - Agarwal, Gina; Pirrie, Melissa; Angeles, Ricardo; Marzanek, Francine; Thabane, Lehana; O'Reilly, Daria
Abstract : Objectives: To evaluate the cost-effectiveness of the Community Paramedicine at Clinic (CP@clinic) programme compared with usual care in seniors residing in subsidised housing. Design: A cost–utility analysis was conducted within a large pragmatic cluster randomised controlled trial (RCT). Subsidised housing buildings were matched by sociodemographics and location (rural/urban), and allocated to intervention (CP@clinic for 1 year) or control (usual care) via computer-assisted paired randomisation. Setting: Thirty-two subsidised seniors' housing buildings in Ontario. Participants: Building residents 55 years and older. Intervention: CP@clinic is a weekly community paramedic-led, chronic disease prevention and health promotion programme in the building common areas. CP@clinic is free to residents and includes risk assessments, referrals to resources, and reports back to family physicians. Outcome measures: Quality-adjusted life years (QALYs) gained, measured with EQ-5D-3L. QALYs were estimated using area-under-the curve over the 1-year intervention, controlling for preintervention utility scores and building pairings. Programme cost data were collected before and during implementation. Costs associated with emergency medical services (EMS) use were estimated. An incremental cost effectiveness ratio (ICER) based on incremental costs and health outcomes between groups was calculated. Probabilistic sensitivity analysis using bootstrapping was performed. Results: The RCT included 1461 residents; 146 and 125 seniors completed the EQ-5D-3L in intervention and control buildings, respectively. There was a significant adjusted mean QALY gain of 0.03 (95% CI 0.01 to 0.05) for the intervention group. Total programme cost for implementing in five communities was C128 462 and the reduction in EMS calls avoided an estimated C256 583. The ICER was C2933/QALY (bootstrapped mean ICER with Fieller's 95% CI was 4850 (2246 to 12 396)) but could be even more cost effective after accounting for the EMS call reduction. Conclusion: The CP@clinic ICER was well below the commonly used Canadian cost–utility threshold of C50 000. CP@clinic scale-up across subsidised housing is feasible and could result in better health-related quality-of-life and reduced EMS use in low-income seniors. Trial registration number: Clinicaltrials.gov, NCT02152891 .